And Still I Rise: Resilience Factors Contributing to Posttraumatic Growth in African American Women. (March 2021) - Mushonga, Dawnsha R.; Rasheem, Shvilla; Anderson, Darlene
Understanding the impact of trauma and resilience has long been of interest to mental health professionals everywhere. However, what is missing in the literature is the unique standpoint of African American women who are often trapped in a traumatic cycle of poverty and intimate partner violence (IPV). Therefore, the purpose of this qualitative study was to understand the lived experiences of African American women surviving IPV and examine resilience factors that may contribute to the development of posttraumatic growth (PTG). Semistructured interviews were conducted with eight African American women survivors of IPV. Thematic analysis revealed six themes that were relative to the development of PTG: spirituality, motherhood, gratitude, prudence, solitude, and selective attention. The emergent themes in this study present the counter narrative of African American women who see both adaptive and maladaptive mechanisms as viable contributors of PTG. This study informs practitioners about various strategies used by economically disadvantaged African American women survivors that may contribute to PTG following traumatic experiences, such as IPV.